Conformational dynamism for DNA interaction in the Salmonella RcsB response regulator. Issue 1 (23rd November 2017) - Casino, Patricia; Miguel-Romero, Laura; Huesa, Juanjo; García, Pablo; García-del Portillo, Francisco; Marina, Alberto
Abstract: The RcsCDB phosphorelay system controls an extremely large regulon in Enterobacteriaceae that involves processes such as biofilm formation, flagella production, synthesis of extracellular capsules and cell division. Therefore, fine-tuning of this system is essential for virulence in pathogenic microorganisms of this group. The final master effector of the RcsCDB system is the response regulator (RR) RcsB, which activates or represses multiple genes by binding to different promoter regions. This regulatory activity of RcsB can be done alone or in combination with additional transcriptional factors in phosphorylated or dephosphorylated states. The capacity of RcsB to interact with multiple promoters and partners, either dephosphorylated or phosphorylated, suggests an extremely conformational dynamism for this RR. To shed light on the activation mechanism of RcsB and its implication on promoter recognition, we solved the crystal structure of full-length RcsB from Salmonella enterica serovar Typhimurium in the presence and absence of a phosphomimetic molecule BeF3 − . These two novel structures have guided an extensive site-directed mutagenesis study at the structural and functional level that confirms RcsB conformational plasticity and dynamism. Our data allowed us to propose a β5-T switch mechanism where phosphorylation is coupled to alternative DNA binding ways and which highlights the conformational dynamism of RcsB to be so pleiotropic.